Genetic factors may load the gun, but environmental factors pull the trigger: MedDiet and DII in rheumatoid arthritis - Açıkalın Göktürk, Büşra; Sanlier, Nevin (Frontiers in Nutrition, 2025)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease that causes progressive joint destruction. It affects ~1% of the world population and is more common in women aged 20–45 years than in men. RA causes involvement of small joints such as the joints of the hands and feet, pain, swelling, stiffness and loss of function in the joints. In recent years, Mediterranean diet and anti-inflammatory diet models have attracted attention in the medical nutrition therapy of patients with RA. These dietary patterns have been suggested to reduce disease risk and complications and improve disease manifestations. Mediterranean and inflammatory dietary patterns contain antioxidant vitamins and minerals, omega-3, polyunsaturated fatty acids and may have effects on inflammation and pain. In addition, dietary patterns may be effective in preventing free radical formation and increased cytokine levels due to their antioxidant and anti-inflammatory properties. In addition, by decreasing inflammatory markers and increasing antioxidant mechanism, it may be effective in reducing the level of disease activity, clinical and biochemical findings and increasing the quality of life. While the Mediterranean Diet and diet inflammatory index (DII) show promise in managing RA, it is important to consider the variability of individual responses to dietary interventions. There are conflicting results regarding the efficacy of the MedDiet in reducing disease activity and further research is needed to establish robust evidence-based dietary recommendations for RA patients. Overall, incorporating dietary strategies with anti-inflammatory properties may offer a valuable addition to conventional RA management and potentially improve patient outcomes and quality of life.